Fifteen new Trichoptera (Insecta) species from Sumatra, Indonesia - Oláh, János; Johanson, Kjell Arne (Zootaxa, 2010)
The following new species are described from the west coast of Sumatra (Indonesia): Dipseudopsis gabiana and Pseudoneureclipsis complexa (Dipseudopsidae); Psychomyia selatana and Tinodes kerinciana (Psychomyiidae); Nyctiophylax anryutah, N. kupirah, and N. tapan (Polycentropodidae); Diplectrona dimagaha, D. tiguna, Hydropsyche pulakita, and Cheumatopsyche urhpirdana (Hydropsychidae); and Oecetis barisan, Setodes pantangulil, S. trikuthia, and S. wirhal (Leptoceridae). In addition, the following species are recorded from Sumatra for the first time: Chimarra briseis Malicky (Philopotamidae); Ecnomus hendersoni Mosely (Ecnomidae); Diplectrona dulitensis Kimmins and Hydropsyche butes Malicky & Chantaramongkol (Hydropsychidae); and Ganonema ochraceellum (McLachlan) (Calamoceratidae). Fourteen more species are recorded, but are previously known from Sumatra.